The assessment of status of Sibam River and Air Hitam River Pekanbaru city Riau Province using pollution index - Yuliati Yuliati; Eni Sumiarsih; Efawani Efawani; Isma Mulyani; Nur El Fajri (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
The quality of the Siak River is gradually deteriorating with the rapid socio-economic development in its tributary watersheds. S. Sibam and Air Hitam are part of the Siak tributaries in the Siak tributary sub-region in Pekanbaru City. The quality of the Sibam and Air Hitam tributaries in the Siak Watershed of Pekanbaru City has been studied to determine the relative pollution level of water quality standards. Water quality measurements were carried out from January to August 2022 at the upstream, middle, and confluence with the Siak River. The pollution level of the Sibam River and Air Hitam River was measured using the pollution index method. The quality of the Sibam River and Air Hitam waters is compared to the quality standards according to The Regulation of Government of the Republicof Indonesia(RGRI) Number 22/2021 Class III. The water quality parameter measured consisted of dissolved oxygen, TSS, pH, BOD, COD, nitrate, nitrite, ammonia, and total phosphate. Pollution index calculations for the Sibam and Air Hitam rivers show light pollution, with index values ranging from 1.75 to 3.57. Nitrite and ammonia concentrations in the Sibam River do not meet quality standards. Whereas in the Air Hitam River, the BOD, nitrite, and ammonia level exceeds the quality standards (RGRI Number 22/2021 Class III). The highest pollution index is in the middle of the river, with settlements on both rivers.Keywords:Pollution IndexWater QualitySibam RiverAir Hitam River